REFLEKSI TEOLOGI HERMENEUTIK DI HARI AIR SEDUNIA 2021 - Simon, John Christianto; Tandirerung, Lidya K.; Abialtar, Abialtar (Jurnal Teologi (Journal of Theology), 2021)
This research raises the issue of water in the framework of the theme of world water day 2021, managing water to maintain life, in a review of hermeneutics theology. The main question to be answered is what is the contribution (study and solution) of hermeneutics theology to the problem of water in order to maintain life? This research includes literature research and is qualitative in nature which aims to construct meaning on selected reading sources. The method used is critical hermeneutic reading on written and selected sources as material to build a discourse on water. Critical hermeneutics is the art of understanding reality through virtue and practical action (phronesis) which starts from self-criticism and raises the morality of living just and good with other creatures, in this case with water. This study finds that through the study of hermeneutics theology, water is a sacred gift of God, namely God’s self-gift for the entire created world. Water is a public theological issue that crosses faiths and cultures, forming a cosmic interfaith and cultural fellowship that fertilizes each other in a sustainable web of life.